Transformasi Pendidikan Sekolah Dasar di Era Digital: Tantangan dan Strategi Pembelajaran Abad ke-21 di SD Negeri 1 Kesesi: Transformation of Elementary School Education in the Digital Era: Challenges and Strategies for 21st-Century Learning at Kesesi 1 Public Elementary School - Aulia Isdiyana; Bagas Mukti Nasrowi (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2026)
The rapid development of digital technology has significantly transformed the educational landscape, particularly in elementary education, which is required to adapt to 21st-century learning demands. This study aims to analyze the transformation of elementary school education in the digital era, focusing on identifying challenges and exploring the implementation of 21st-century learning strategies. This research employed a qualitative descriptive approach, with data collected through in-depth interviews involving an elementary school teacher. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that digital-based learning has been implemented through the use of technology such as laptops, projectors, and instructional videos, although its application remains inconsistent. Learning activities have shifted toward student-centered approaches, emphasizing active participation through discussions, question-and-answer sessions, and educational games. However, several challenges persist, including limited infrastructure, unstable internet connectivity, and varying levels of students’ digital literacy. Despite these constraints, teachers demonstrate adaptive efforts by adjusting teaching strategies and improving their digital competencies. In conclusion, the transformation toward digital learning has been initiated but requires further optimization. This study contributes to the development of elementary education by highlighting the importance of technological integration, teacher readiness, and institutional support in enhancing effective and sustainable digital learning practices